Economists and the Economy - Laband, David N.; II, William F. Shughart; Tollison, Robert D. (The Review of Economics and Statistics, 1990)
Using data from a sample of the economic literature published over the years 1950 through 1988, we find substantial support for an environmental theory of idea entrepreneurship among economists. In particular, we show that the percentage of economic articles devoted to the topics of inflation and employment are related directly to the actual inflation and unemployment rates in the economy and indirectly to the growth rate of aggregate real income. Moreover, we are able to provide evidence of undirectional causality running from changes in the economic environment to changes in the composition of the economic literature. Copyright 1990 by MIT Press.